Prognostic value of Bax, Bcl-2, p53, and TUNEL staining in patients with radically resected ampullary carcinoma. Issue 2 (27th January 2005) - Santini, D; Tonini, G; Vecchio, F M; Borzomati, D; Vincenzi, B; Valeri, S; Antinori, A; Castri, F; Coppola, R; Magistrelli, P; Nuzzo, G; Picciocchi, A
Abstract : Background: There is a lack of data in the literature concerning the identification of potential prognostic factors in ampullary adenocarcinoma. Aims: To examine the prognostic significance of Bax, Bcl-2, and p53 protein expression and the apoptotic index in a large cohort of uniformly treated patients with radically resected ampullary cancer. Methods: All patients with a pathological diagnosis of ampullary cancer and radical resection were evaluated. Expression analysis for p53, Bax, and Bcl-2 was performed by immunohistochemistry. Apoptotic cells were identified by terminal deoxynucleotidyl transferase mediated dUTP nick end labelling (TUNEL). Results: Thirty nine tumour specimens from patients with radically resected ampullary adenocarcinoma were studied. A positive significant correlation between Bax and p53 expression was found by rank correlation matrix (p < 0.001). A trend towards a positive correlation was found between the apoptotic index and p53 expression (p = 0.059). By univariate analysis, overall survival was influenced by Bax expression, p53 expression, and TUNEL staining (p = 0.001, p = 0.01, and p = 0.03, respectively). Bcl-2 expression did not influence overall survival in these patients (p = 0.55). By multivariate Cox regression analysis, the only immunohistochemical parameter that influenced overall survival was Bax expression (p = 0.020). Conclusions: These results provide evidence that apoptosis may be an important prognostic factor in patients with radically resected ampullary cancer. This study is the first to assess the clinical usefulness of Bax expression in radically resected ampullary cancer.